Tratamiento de aguas de drenaje de mina mediante biocoagulación con Caesalpinia spinosa (Guarango) - Guzmán Andrade, Stephanie Michelle (2020)
For the present study, Guarango Caesalpinia spinosa, a plant species was selected for the production of biocoagulant, due to having a composition made of tannins up to 60 percent, which are hydrolysable. These biomolecules confer its biocoagulation capacity of Caesalpinia spinosa. It is widely distributed regionally, and has a high capacity to adapt to hostile environments. Previously conducted studies on Caesalpinia spinosa were successfully carried out for the removal of COD, TSS and turbidity. However, all were conducted in waters with neutral to basic pH, for this reason, the mining industry was selected. Mining is one of the most complex activities along its production chain, because of the extraction of minerals; highly polluting effluents are generated, called drains. These drains can have a very acidic pH, depending on its composition, mainly depending on amount of sulphurous minerals present in the effluents. These acidic effluents pollute surface and underground effluents, altering wildlife. For this reason, 3 mining industries were selected, which have different deposits, all 3 with different pH levels, which were: neutral, acid and very acidic. The 3 mines underwent a pre-application study before applying the biocoagulant treatment using physical chemical parameters. For the preparation of the biocoagulant, two methodologies were unified, SLE Solid Liquid Extraction and MAE Microwave Assisted Extraction, once the biocoagulant was prepared, optimal dosing tests were performed individually for each type of mine and later in a general way. To determine the efficiency of the biocoagulant, two doses of biocoagulant were proposed, one of them the general optimal dose, which was 2 ml and 4.5 ml, compared with a chemical coagulant PAC and a blank test. These treatments were performed 3 analyzes to determine their efficiency. First, the calculation of the removal efficiency by percentage, followed by an analysis of national regulatory compliance for surface effluents and international regulations for discharge compliance to underground effluents, and finally, an analysis of statistical significance was performed. In Conclusion, T2 4.5 ml of biocoagulant was the best treatment, surpassing the chemical coagulant PAC, in the 3 studies carried out. The parameters in which the best effects were obtained were the following: in Mine No.1 pH 7.33, SST 92.02 percent, turbidity 79.59 percent, EC 51.19 percent and color 92.77 percent; in mine No. 2 pH 5.43, SST 84.58, turbidity 97.70 percent, CE 33.75 percent and color 89.85 percent; and lastly mine No. 3 pH 3.88, SST 95.33, turbidity 91.88 percent, CE 33.75 and color 67.27 percent. Of all data obtained through the T2 treatment application, the results of Mine No 1. was the most efficient in its 3 analysis removal efficiency, regulatory compliance, statistical significance.